TEPUNG KAYA PROTEIN DARI KORO KOMAK SEBAGAI BAHAN PANGAN FUNGSIONAL BERINDEKS GLISEMIK RENDAH [Protein Rich Flour from Hyacinth Bean as Functional Food Ingredient with Low Glycemic Index] - Ahmad Nafi’; Wiwik Siti Windrati; Andri Pamungkas; Achmad Subagio (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
ABSTRACT Protein-rich flour (PRF) produced from Hyacinth bean (Lablab purpureus (L) Sweet) shows good potency as a functional food ingredient. The PRF was extracted from hyacinth bean using water followed by protein precipitation at its isoelectric point. The precipitate was neutralized using 1 N NaOH and the slurry was dried, ground and sieved. The objective of this research was to characterize the nutritive value of PRF i.e., protein content and amino acid profile, trypsin inhibitors activity, content of vitamins B1 and B2, the amylose and amylopectin ratio of starch and its glycemic index. The results showed that the PRF contained high protein (58.4±4.5%). The major amino acid was glutamic acid, while methionine was found as the limited amino acid of the PRF. The activity of trypsin inhibitor was low (20.4±1.6 unit/g). Moreover, PRF contains 0.2 and 3.6 mg/100 g of vitamins B1 and B2 respectively. With a high ratio of amylose (30.0±2.0%) and high content of resistance starch (7.97 g/100 g), the PRF showed a low glycemic index (43.50). Based on its characteristics, this PRF can be promoted as a new food ingredient, especially for diabetic diet. Keywords: glycemic index, nutritive value, protein rich flour Komak (Lablab purpureus (L) Sweet)